ANALISIS PENERAPAN PERENCANAAN PAJAK PENGHASILAN BADAN GUNA MEMINIMALKAN PEMBAYARAN PAJAK PENGHASILAN BADAN PADA PT. BUMI SARANA BETON - Andi Rustam; Mira Mira; Aswar Aswar; Ika Sartika (Jurnal Riset Perpajakan: Amnesty, 2019)
research is done with the aim to know how to apply the tax planning conducted by PT Bumi Sarana Beton To minimize the burden of the company's income tax. In this study, the literature and observations review was by conducting research on the field through live interviews and data retrieval, related documents from the company as well as the use of books, and internet media. The data obtained in the analysis using a descriptive analysis is to exercise data of the commercial financial statements and the existing fiscal reports. The results showed that the application of tax planning by the company has been in accordance with the prevailing tax laws and with the implementation of taxation planning hence the saving of income tax expenses amounted to Rp 133,456,401.